Calculation of The Cost of Underground Mining Activities on Tunnel 9 PT. Allied Indo Coal Jaya (EarthCare, 2022)
Allied Indo Coal Jaya is one of the mining companies with types of coal mining materials. Mining methods used by PT. Allied Indo Coal Jaya is an open-pit mining and underground mining method. In the underground mining method, the adding system used is a room and pillar where coal extraction activities are carried out semi-conventionally and detonation. Blasting is carried out to support coal production activities to achieve the targets set by the company. However, the problem faced today is the non-achievement of the production target in Tunnel 9, which is 33 tons of coal while the actual production is 18.70 tons of coal. The non-achievement of production targets due to the geometry of blasting is inadequate for the dismantling of coal with the desired target. Based on the calculation of the dimensions of mine progress, it was found that the coal production yield was 17.03 tons of coal, while for blasting activities using the theory of R. L. Ash, it was found that the blasting result was 12.60 tons of coal. With blasting activities that were able to dismantle 12.60 tons of coal and the number of workers as many as 6 people, a mining profit of Rp.52,435,619.27 was obtained. Increased blasting twice daily and the addition of 8 personnel in Tunnel 9 are the answers to raising coal productivity. The addition of blasting activities and the number of workers can increase coal products to 35.20 tons of coal with a mining profit of Rp. 108,407,142,864.